Memanfaatkan Petunjuk Ilahi Dalam Menelusuri Lorong-Lorong Kehidupan (Kajian Tafsir Tematik) - Otong Surasman (Kopertais Wilayah I DKI Jakarta dan Banten, 2020)
How important is life in modern times, even though advances in technology are almost at their peak, so that they continue to explore the noble values of Islamic teachings, especially those closely related to guidance or guidance. Because in reality in everyday life, most people do not seem to understand the instructions that Allah SWT gives. The real evidence is that there are still many human behaviors that violate the norms of life, by corrupting, deceiving, hurting and abusing others, depriving others of their rights, and many other irregularities. Which if analyzed in full with wisdom, it means that Allah's guidance in the form of instincts and senses alone are not used by humans, even though these instinctual and sensory guidance are the initial or basic steps, before entering the next instructions in the form of guidance in the form of reason and religion. In the instinctual and sensory guidance there is already a human potential that is able to distinguish what is good and what is bad, which is assisted by a sense guide. Humans should be able to do good and try to distance themselves from bad deeds. With the hope of the presence of this article, it will help humans to try to spread virtue values in everyday life, so that one day a life filled with peace can be created